Additional file 2 of Identification of SLC22A17 DNA methylation hotspot as a potential biomarker in cutaneous melanoma - Alessandro Lavoro (13835752) (2024)
Supplementary Material 2: UCSC visualization of the SLC22A17 locus. The SLC22A17 CG probesets (Infinium 450 K Bead array) included in the bioinformatic analysis are displayed. The sequences used for bisulfite-Sanger sequencing and PCR-based MSRE analyses were aligned to the SLC22A17 genomic sequence